'I Want to Persuade You!' – Investigating the effectiveness of explicit persuasion concerning attributes of the communicator and the marketing campaign. (2nd October 2017) - Schindler, Simon; Reinhard, Marc-André; Grünewald, Felix; Messner, Matthias
Abstract: In explicit persuasion, the communicator states explicitly a desire to persuade the consumer. By referring to an attributional approach, social engagement was simultaneously explored as a beneficial communicator attribute, while cause-related marketing (CRM) was addressed as a boundary condition. In an experiment, we varied the persuasion strategy (explicit vs. implicit), the communicator's prior experience with social engagement (yes vs. no), and the specific marketing strategy (CRM vs. non-charity marketing). As expected, in the non-charity marketing condition, explicit (vs. implicit) persuasion was more effective when the communicator had prior experience in social engagement. In the CRM condition, explicit (vs. implicit) persuasion was less effective when the communicator had prior experience in social engagement; when no prior experience was reported, persuasiveness increased.